2019
DOI: 10.1039/c9fo01635j
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effects of hydroalcoholic extracts from an ancient apple variety ‘Mela Rosa dei Monti Sibillini’ against renal ischemia/reperfusion injury in rats

Abstract: The purpose of this work was to investigate the effect of hydroalcoholic extracts from the peel and pulp of a traditional apple variety of central Italy on the damage caused by renal ischemia/reperfusion injury in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…In the present study, CCl4 administration increased the serum levels of ALT, AST, ALP. Yousefi-Manesh et al have reported that APE prevented kidney injury induced by ischemia and reduced oxidative stress [8]. In the present study, the pretreatment of rats with both APE and APP obtained from the same Italian apple variety (Mela Rosa dei Monti Sibillini) significantly reduced the serum levels of ALT, AST and ALP compared to the CCl4 group suggesting a protective effect.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In the present study, CCl4 administration increased the serum levels of ALT, AST, ALP. Yousefi-Manesh et al have reported that APE prevented kidney injury induced by ischemia and reduced oxidative stress [8]. In the present study, the pretreatment of rats with both APE and APP obtained from the same Italian apple variety (Mela Rosa dei Monti Sibillini) significantly reduced the serum levels of ALT, AST and ALP compared to the CCl4 group suggesting a protective effect.…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, CCl 4 administration increased the serum levels of ALT, AST, ALP. Yousefi-Manesh et al have reported that APE prevented kidney injury induced by ischemia and reduced oxidative stress [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Annurcoic acid is a more bioavailable form of ursolic acid, given its chemical resemblance and the presence of an additional hydroxylic group. Ursolic acid is an important inhibitor of the NF-kB-mediated inflammatory response [21].…”
Section: Discussionmentioning
confidence: 99%